TEACHER CREATIVITY IN THE CLASSROOM MANAGEMENT - HUSIN, AZIZAH (Sriwijaya University Learning and Education International Conference, 2016)
Creativity needs to be done by the teacher in the learning task. With creativity,learning goals would be more easily achieved. Creativity of the teacher in teachingreforms ideas, practices, and educational products. Renewal was about somethingtotally new, combined, or modification of, or the development of new forms of theold to. Classroom management for teachers who do this need modified so that theprocess learning and teaching fun and students are motivated to learn. Learningcomponent that is directly related to the learning process in the classroom and needto be considered in the management class is primarily instructional materials, media,methods, teacher, student, classroom atmosphere, and arrangement of allcomponents to run. Interaction this raises the learning dynamics. These dynamicscan vary its shape and determine the quality and effectiveness of learning. Itrequired creativity in managing classroom teacher in order to target the achievementof goals.